Algorithmic Activity as an Improvement Vector of the Vocational Training of the Future Social and Humanitarian Sciences Teachers - Сметаніна, Людмила Сергіївна (Educological discourse, 2014)
In this article the features of professional education of future teachers of social studies and humanities are analysed. The necessity of the algorithmic activity organization is proved as a powerful tool for improving their training.